2022
DOI: 10.3393/ac.2021.00899.0128
|View full text |Cite
|
Sign up to set email alerts
|

A small, low-grade rectal neuroendocrine tumor with lateral pelvic lymph node metastasis: a case report

Abstract: Rectal neuroendocrine tumors (NETs) are typically small lesions that are confined to the submucosa and have favorable behavior at the time of diagnosis. Local endoscopic or surgical resection is recommended because lymph node metastasis is very rare. In this report, we present the case of a 36-year-old male presenting with an incidentally found rectal mass during screening colonoscopy. Pathologic examination of the primary tumor revealed a 9-mm grade 1 NET with submucosal invasion and no significant aggressive… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2022
2022
2025
2025

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 14 publications
0
4
0
Order By: Relevance
“…Both short-and long-term outcomes in patients who undergo curative resection for rectal NETs are largely unknown, and even less is known about LPLN metastasis in rectal NETs [18]. Although there are a few reports on LPLN metastasis in rectal NETs [12,14,18,19], no studies have addressed the clinical features and prognosis of LPLN metastasis in patients with rectal NETs. LPLN metastasis in rectal NETs is a rare occurrence; currently, there are no de nite criteria for diagnosing LPLN metastasis and no exact indication for LPLN dissection in patients with rectal NETs [4].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Both short-and long-term outcomes in patients who undergo curative resection for rectal NETs are largely unknown, and even less is known about LPLN metastasis in rectal NETs [18]. Although there are a few reports on LPLN metastasis in rectal NETs [12,14,18,19], no studies have addressed the clinical features and prognosis of LPLN metastasis in patients with rectal NETs. LPLN metastasis in rectal NETs is a rare occurrence; currently, there are no de nite criteria for diagnosing LPLN metastasis and no exact indication for LPLN dissection in patients with rectal NETs [4].…”
Section: Discussionmentioning
confidence: 99%
“…One is along the superior rectal artery and inferior mesenteric artery, draining into the LNs around the abdominal aorta; the other is along the middle rectal artery, entering the obturator and internal and external iliac LNs, i.e., the lateral pelvic lymph nodes (LPLNs). LPLN metastasis of rectal NETs is rare, and only a few corresponding case reports have been published [12][13][14]. Among cases of rectal cancer, the survival of patients with LPLN metastasis was poorer than that of patients without LPLN metastasis [15][16][17], suggesting that LPLN metastasis can also be a poor prognostic factor in rectal NETs.…”
Section: Sohn Et Al Have Reported That Ln Metastasis Affects Survival...mentioning
confidence: 99%
“…The likelihood of lymph node metastasis increases with tumor size. In tumors smaller than 10mm, lymph node metastasis is a rare result, with an incidence of 1% ~ 10% ( 31 33 ). The rectal NEN with a maximum diameter of 1-2 cm has a lymph node metastasis rate of about 30% at the time of diagnosis, and about 40% in those ≥20 mm ( 27 , 34 ).…”
Section: Discussionmentioning
confidence: 99%
“…In general, rNENs are well differentiated small tumors with a fairly good prognosis, but they also show variations of larger tumor size, metastasis, and severe prognosis (11). A case report found that radiology of a lowgrade rNEN in a 36-year-old male revealed a suspected 2.6 cm mesenteric lymph node metastasis and multiple left internal iliac lymph node metastases (12).…”
Section: Introductionmentioning
confidence: 99%